The distributional effects of direct college costs - Jonathan Gemus (Uppsala University, Department of Economics, 2010)
This paper examines the distributional impacts of direct college costs - that is, whether the response of educational decisions to college costs varies by student characteristics. The primary obstacle in estimating these effects is the endogeneity of schooling costs. To overcome this issue, I use two measures of direct costs that are plausibly exogenous: living within commuting distance to a university and the elimination of the Social Security Student Benefit Program in the United States. Both sources of variation indicate that lower ability students are the most responsive to changes in college costs. In contrast, I find that the effect of both cost measures on college attendance and graduation does not substantially vary by family income, parent education, race or gender.
urn:nbn:se:uu:diva-133958
Keywords: I20; I28; J24; 330; Schooling Costs; Educational Attainment; Financial Aid Policy; Studienfinanzierung; Bildungsinvestition; Bildungsabschluss; Bildungsverhalten; USA